Influence of Strategic Management Practices on the Performance of Uganda Police Force - Okurut, Micheal; Deya, Jared (European Journal of Business and Strategic Management, 2023)
Purpose: The aim of the study was to examine the influence of strategic management practices on the performance of Uganda police force. Methodology: A descriptive research design was used in which quantitative data collection approach was applied. The population of the study was 96 from which a sample of 63 was selected. The study used both stratified random sampling and purposive sampling to select staff members in their respective strata (top police officers, middle-level officers, and low-level officers). A structured questionnaire in a five likert scale format was used to collect data from the respondents. The collected data was analyzed by both descriptive and inferential statistics with the aid of the Statistical Package for Social Sciences (SPSS) version 24. Descriptive analysis involved frequencies and percentages for demographic data of respondents. Inferential statistics in the form of correlation and multiple regression analyses were employed. Findings: Strategic management hold distinct positive relationships with performance of Uganda police. As strategic management increase, performance is likely to improve. These findings emphasize investing in strategic management initiatives to enhance overall organisational performance. The Uganda Police Force is regularly interactions with civilians, fostering increased citizen trust through community policing, which in turn enhances its effectiveness in law enforcement. There's high confidence in the police force's effective collaboration with experts, and collaborative projects are generally seen as successful. There are also community support for collaborative initiatives within the force. There is a well-established and highly effective crisis management plan in place, known and understood by the majority of its personnel. Uganda police force has an extensive staff capacity building plan in place, reflecting strong confidence in its commitment to enhancing personnel skills and knowledge. Unique Contribution to Theory, Practice and Policy: Theory of the public enforcement of law can be used to anchor future studies on the police administration sector. The study recommends that Uganda police force should address concerns about salary structures and remuneration fairness, as there is a substantial perception gap among personnel. Additionally, the force should maintain its commitment to personnel development through training and capacity building, given its positive impact on performance. Uganda Police Force should prioritize public awareness campaigns.